Avaliação espaço-temporal da disponibilidade hídrica subterrânea do município de São José do Rio Preto - Lourencetti, Josiane [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
With the growing increase use of underground water resources for different types of uses, verified the need to evaluate the progressive variation of the level of water in the underground reserves. Due of the urbanization process, modify the characteristics of the natural landscape, implying in the soil impermeability in large areas, reducing the conditions of infiltration and recharge of groundwater sources. In this context, studies aim to establish control of the extraction of groundwater, aiming at the conservation of the quantitative and qualitative aspects of natural aquifers. The excessive exploitation of groundwater already poses risks to the public water supply in some Brazilian municipalities, with the necessity of implementation of appropriate management to ensure the sustainable use of water resources. This work analyzed the behavior of the potentiometric level Bauru aquifer the municipality of Sao José do Rio Preto, due to the sharp increase in drilling wells and the need for delimitation of areas potentially critical groundwater resources. The research focused on the manipulation of data and information necessary to represent the variations of the static level of the Bauru aquifer, and quantify the growth of the urban and the population municipality. The data referring aquifer were collection in the Information System of Groundwater (SIAGAS) and the Department of Water and Electrical Energy (DAEE) Araraquara, data relating of the relief of the terrain and ground cover, collected by the EMBRAPA, INPE, IBGE and image viewer satellite Google Earth and, the population data by the IBGE. With the assistance of software AutoCAD, Excel, Google Earth, Spring and Surfer were constructed maps of land cover and DEMs (Digital Elevation Models) terrain and static level of the aquifer, as well as illustrative graphics, for representation and quantification of variations in the period 1972-2012. The results demonstrated that the uncontrolled increase of urbanization had a direct influence under the potential underground water, as well as, the excessive extraction of groundwater, which contributed to the occurrence of the downgrade of 10 meters from Bauru Aquifer, observed in the 2000s. The Bauru Aquifer, the main source of municipal supply, presents itself limited and may directly jeopardize the public supply system, which uses 41.2% of the 43,818 m³/d removed from the source.

Com o crescente aumento da utilização do recurso hídrico subterrâneo para diversos tipos de usos, verifica-se a necessidade de avaliar a variação progressiva do nível da água nas reservas subterrâneas. Em decorrência do processo de urbanização, modificam-se as características da paisagem natural, implicando na impermeabilização do solo em grandes áreas, diminuindo as condições de infiltração e recarga dos mananciais subterrâneos. Neste contexto, estudos almejam estabelecer um controle da extração de água subterrânea, visando à conservação dos aspectos quantitativos e qualitativos naturais dos aquíferos. A explotação excessiva de água subterrânea já apresenta riscos para o abastecimento público em alguns municípios brasileiros, sendo necessária a implantação de métodos adequados de gerenciamento para garantir o uso sustentável do recurso hídrico. Neste trabalho foi analisado o comportamento do nível potenciométrico do Aquífero Bauru no Município de São José do Rio Preto, devido ao intenso aumento na perfuração de poços e à necessidade de delimitação de áreas potencialmente críticas de recursos hídricos subterrâneos. A pesquisa enfocou a manipulação de dados e informações necessárias para representar as variações do nível estático do aquífero Bauru, bem como quantificar o crescimento da malha urbana e da população do município. Os dados referentes ao aquífero foram coletados no Sistema de Informações de Águas Subterrâneas (SIAGAS) e no Departamento de Águas e Energia Elétrica (DAEE) de Araraquara, os dados referentes ao relevo do terreno e cobertura do solo, coletados junto à EMBRAPA, INPE, IBGE e visualizador de imagens de satélite Google Earth e, os dados populacionais junto ao IBGE. Com o auxílio dos softwares AutoCAD, Excel, Google Earth, Spring e Surfer, foram construídos mapas da cobertura do solo e MDEs (Modelos digitais de Elevação) do terreno e do nível estático do aquífero utilizando técnicas de interpolação, bem como gráficos ilustrativos, para representação e quantificação das variações ocorridas no período de 1972 a 2012. Os resultados demonstraram que o aumento desordenado da urbanização teve influência direta sob o potencial hídrico subterrâneo, como também, a extração excessiva de água subterrânea, que contribuíram para a ocorrência do rebaixamento de 10 metros do Aquífero Bauru, observado na década de 2000. O Aquífero Bauru, principal fonte de abastecimento municipal, se apresenta limitado, podendo comprometer diretamente o sistema de abastecimento público, que utiliza 41,2% dos 43.818 m³/d retirados do manancial.
Keywords: Águas subterrâneas; Aquiferos; Abastecimento de água; Recursos hídricos - Desenvolvimento; Groundwater